2015
DOI: 10.1111/jch.12484
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Visit‐to‐Visit Systolic Blood Pressure Variability: A Meta‐Analysis of 77,299 Patients

Abstract: In recent clinical investigations, visit-to-visit systolic blood pressure (SBP) variability was proven as a predictor of cardiovascular events and all-cause mortality. However, inconsistent results exist in this association. A meta-analysis of 13 prospective studies was conducted to evaluate the prognostic value of visit-to-visit SBP variability by different parameters in 77,299 patients with a mean follow-up of 6.3 years. The pooled age-and mean SBP-adjusted hazard ratios (HRs) for all-cause mortality were 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 48 publications
4
55
1
2
Order By: Relevance
“…Esta variabilidad intraindividual en varias medidas fisiológicas ha cobrado cada vez más interés en los últimos años debido a que tanto la disminución de la variabilidad de la frecuencia cardíaca como el aumento de la variabilidad de la presión arterial estuvieron reiteradamente relacionados con resultados adversos como eventos vasculares, deterioro cognitivo, y mortalidad. [2][3][4][5][6] Sin embargo, poco se sabe acerca de la variabilidad del colesterol, la cual puede ser considerable aún a diario. 7,8 La evidencia reciente indica que, en sujetos con arteriopatía coronaria, una mayor variabilidad entre una visita y otra en el colesterol de lipoproteínas de baja densidad (LDL-C) está asociada con mayores riesgos de eventos coronarios y otros eventos cardiovasculares, accidente cerebrovascular, y mortalidad independientemente de los niveles medios de LDL-C. 9 Actualmente se desconoce si la variabilidad del LDL-C entre una visita y otra está asociada con el rendimiento cognitivo.…”
Section: Conclusionesunclassified
“…Esta variabilidad intraindividual en varias medidas fisiológicas ha cobrado cada vez más interés en los últimos años debido a que tanto la disminución de la variabilidad de la frecuencia cardíaca como el aumento de la variabilidad de la presión arterial estuvieron reiteradamente relacionados con resultados adversos como eventos vasculares, deterioro cognitivo, y mortalidad. [2][3][4][5][6] Sin embargo, poco se sabe acerca de la variabilidad del colesterol, la cual puede ser considerable aún a diario. 7,8 La evidencia reciente indica que, en sujetos con arteriopatía coronaria, una mayor variabilidad entre una visita y otra en el colesterol de lipoproteínas de baja densidad (LDL-C) está asociada con mayores riesgos de eventos coronarios y otros eventos cardiovasculares, accidente cerebrovascular, y mortalidad independientemente de los niveles medios de LDL-C. 9 Actualmente se desconoce si la variabilidad del LDL-C entre una visita y otra está asociada con el rendimiento cognitivo.…”
Section: Conclusionesunclassified
“…The majority of studies (21,22) have analysed sensitivity of many different parameters of visit-to-visit BPV concerning the estimation of prediction of cardiovascular events (CVE): standard deviation, standard deviation independent of the mean (SDIM), coefficient of variation (CV), successive variation (SV), average real variability (ARV), range. We followed the standard deviation of SBP, as it was the simplest and the best indicator of future CVE due to the fact that other parameters of BPV were closely correlated and give similar reflections of BPV.…”
Section: Discussionmentioning
confidence: 99%
“…Prospektivna studija je obuhvatila tri posete u ambulanti za hipertenziju tokom perioda prać enja od 22 …”
Section: Sa Prevalencijom Gojaznosti I Svih Prateć Ih Zdravstvenih Riunclassified
“…12 It is possible that higher levels of SD BPV increase stroke risk in population samples 16 and that CV-BPV is less strongly related to stroke risk than SD BPV. The meta-analysis by Tai et al 20 showed that a 1% increased risk of stroke was attributable to a 1 mm Hg increase in SD BPV; however, only 2 included studies used this method. Another difference with prior research is that we included participants without cardiovascular comorbidities, whereas several prior studies have included participants with varying levels of stroke risk.…”
Section: -25mentioning
confidence: 99%
“…The meta-analysis by Tai et al 20 showed that no prospective cohort study has used the coefficient of variation method (CV-BPV) in relation to stroke. Intraindividual fluctuations in BP over 4 years with measurements at 2-year intervals was calculated using CV-BPV (please see online-only Data Supplement).…”
Section: Assessment Of Drug Exposure and Bpmentioning
confidence: 99%